Upaya Peningkatan Keprofesionalan Guru Kelas Tinggi dalam Menyusun Diktat Pelajaran Melalui Bimbingan Kelompok di SD Negeri 07 Mancuang Semester II (Dua) Tahun Pelajaran 2021/2022 - Erma Ariani (Journal on Education, 2022)
This study aims to disclose information and discuss the Efforts to Improve the Professionalism of High Class Teachers in Developing Diktat Lessons through Group Guidance at SD Negeri 07 Mancuang Semester II (Two) Academic Year 2021/2022. The type of research carried out is School Action Research. The research was conducted at SD Negeri 07 Mancuang, Agam Regency. This research was carried out in the Even Semester of the 2021/2022 Academic Year, starting from February to May 2022. The research subjects were 5 teachers who were assisted by the academic year 2021/2022. The research procedure consisted of two cycles with four stages of research starting from planning, implementing, observing and reflecting. Data collection techniques using instruments and observation sheets. The collected data were analyzed using the percentage formula. The results of the research on the average of the first cycle obtained the sufficient category to obtain an average of 3.1 with a percentage of 62.5%. It can be concluded that the ability of teachers to compose lesson instructions is still in the sufficient category, while teachers who are in the good category are only 1.6 or 32.5%. In the implementation of cycle 2 of the 8 aspects mentioned above, it can be concluded that almost all teachers have understood the components and systematics in preparing lesson instructions. Based on the results of the research described above, it can be concluded that through group guidance, teachers can improve the ability of teachers in preparing the Diktat Lessons at SDN 07 Mancuang.